The Impact of Profitability, Leverage and Non-Performing Loan on Banking Stock Return - Irman Firmansyah (SMART Insight, 2022)
This study aims to investigate several factors that influence stock returns on banks listed on the Indonesia Stock Exchange, including profitability, leverage, and Non-Performing Loans. Profitability is measured by net profit margin, leverage is measured by debt to equity ratio, and non-performing loans are a proxy of the amount of bad credit. The method used in this study is a quantitative method with research data obtained from 2014 to 2017. The analysis uses panel data regression analysis. The results showed that Net Profit Margin had no significant effect on Stock Returns, while leverage and Non-Performing Loans had a significant effect on Stock Returns.